Organizational Stress and Its Impact on Organizational Commitment of Industrial Goods Firms in Nigeria - EMMANUEL IGBOMOR (Ekonomika a Spoločnosť)
The study examined the relationship between organizational stress and organizational commitment among employees in industrial goods firms in Nigeria. The main objectives of the study were to investigate the effects of workload stress, work-life balance stress, job security stress, and job control stress on organizational commitment. The study employed the use of primary data sourced from questionnaires distributed to employees of industrial goods firms in Warri, Delta State, Nigeria. The data collected were analyzed using descriptive statistics, Cronbach's alpha, and linear regression analysis. The findings revealed that workload stress and work-life balance stress have significant positive effects on organizational commitment, whereas job security stress and job control stress do not have significant effects. The study therefore recommended that management (industrial goods firms in particular) should formulate and implement strategies/programs (e. g. flexible work arrangement, good employee perk, recognition and benefits, health and wellness initiatives, job stability) intended to provide more support for the employees to carry out their responsibilities/task without experiencing any form of difficulties/challenge that will later result to a negative stress. This will help in sustaining and enhancing the commitment level of employees.